HUBUNGAN ANTARA STATUS GIZI DAN TINGKAT ASUPAN ZAT GIZI DENGAN SIKLUS MENSTRUASI PADA REMAJA PUTRI DI KECAMATAN KEDUNGBANTENG KABUPATEN BANYUMAS - Dita Noviyanti; Endo Dardjito (Jurnal Gizi dan Pangan Soedirman, 2018)
Background: Menstrual disorders often occur among adolescent girls. Menstrual disorder due to several factor including nutritional status, age, physical activity, nutrients intake, disease, stress and influence of cigarettes . Objective: To examined the association between nutritional status and level of nutrients intake with menstrual cycle among aldolescent in Distric Kedungbanteng Banyumas. Methods: Design research is analytic observation with cross sectional approach. Sampling technique used purposive sampling and obtained 69 respondent adolescent girls. The technique of data colelection used menstrual cycle questionnaire, antropometric, food recall 2x24 jam, food picture and food model. Result: There is 40.6% respondent have an abnormal menstrual cycle. Nutritional status (11.6%) classified abnormal. Energy intake (91.3%), carbohydrate (94.2%) protein intake (89.9%) and fat intake (85.5%) classified an abnormal. Based on analysis of Chi-Square test, there is a significant relation between fat intake with menstrual cycle (p=0.041). Conclusion: Fat intake associated with menstrual cycle..